Nilai Filosofis Makanan Tradisional Etnik Betawi untuk Pendidikan Karakter - Humaira, Adinda Hanna; Suswandari, Suswandari; Gunawan, Rudy (Universitas Hamzanwadi, 2026)
Traditional food not only serves to fulfill biological needs, but also contains cultural values that reflect the identity of an ethnic group, including the Betawi ethnic group. Amidst the currents of globalization and modernization, traditional culinary heritage is increasingly marginalized, even though it contains a philosophy of life, social values, and moral teachings that have the potential to be transformed into character education. This study aims to identify the types of traditional Betawi ethnic food in the Kemang area as the research location, including snacks, heavy meals, and drinks, and analyze philosophical values that can support character formation. This study uses a Qualitative approach with the Ethnography method by Spradley, the data analysis technique used is